Childhood rosacea. - Barile, F.; De Meo, M.; Garofalo, L. (European Journal of Pediatric Dermatology, 2005)
Rosacea usually affects adults in the third-fifth decade and prevails in females with a 3/1 ratio as compared with males. However, it may also affect children (1, 2, 4). In childhood, rosacea is never responsible for rhinophyma, whereas the eye is often affected, sometimes severely (4). The eye is often involved before the onset of skin lesions with recurrent chalazion, blepharoconjunctivitis, keratitis, episcleritis and uveitis (4). This is why some Authors advise an ophthalmological consultation in all cases of rosacea, especially in children. Demodex folliculorum is present mainly in pustular forms (3), but sometimes, as our case shows, even precociously when pustules lack. Its pathogenetic role in rosacea is debated. Antibiotics are the first-choice treatment of rosacea. Tetracycline, which is the most effective systemic antibiotic, cannot be used in the first 8 years of age.